The Blossom sisters [compact disc, unabridged] - Michaels, Fern (Brilliance Audio, 2013)
Gus Hollister owes all his success to his feisty grandmother, Rose, and he knows it. It was Rose and her two sisters, Iris and Violet, who raised Gus, sent him to the best schools, and helped him start his own accounting business. Rose even bought the house Gus lives in with his wife, Elaine. But now, Gus stands to lose everything; his home, his car, and his business.